Gambling in COVID-19 in the Ukraine: Stress, Depression and Anxiety - Salnikova Аліна (Psychosomatic Medicine and General Practice, 2021)
This study sought to explore the initial change in depression, anxiety, and stress in gamblers in Ukraine. Results indicate that depression, stress, and anxiety are increasing regardless of gambler status; however, the mere fact that increases are general, should not detract from the elevated levels of depression, stress, and anxiety experienced by those experiencing gambling harm. This is a conference abstract from the III Scientific-practical conference "Psychosomatic medicine: science and practice".